Ultrasound-Accelerated, Concise, and Highly Efficient Synthesis of 2-Oxazoline Derivatives Using Heterogenous Calcium Ferrite Nanoparticles and Their DFT Studies - Anjaneyulu Bendi; Shalu Atri; G. B. Dharma Rao; Mohd Jamshaiya Raza; Nutan Sharma (Journal of Chemistry)
A rapid and operationally simple approach for synthesising biologically relevant 2-oxazoline derivatives has been developed through highly efficient ultrasound-promoted coupling reactions of thioamides and amino alcohols using calcium ferrite nanoparticles as heterogeneous catalysts. The major advantage of using ultrasound irradiation lies in the drastic reduction of reaction time as compared with conventional stirring. Furthermore, quantum chemical investigations for the synthesised 2-oxazoline derivatives have been carried out at the DFT/B3LYP/6-311 + G (d, p) level of theory to predict the optimized geometry. The molecular properties such as bond lengths, bond orders, Milliken charges, frontier molecular orbitals, global reactivity descriptors, molecular electrostatic potential map, and thermodynamic parameters of all the compounds have also been reported at the same level of theory.